Two-layer crystallization of amorphous YMnO3 thin films on Si(100) substrates - Yoo, DC; Lee, JY; Kim, IS; Kim, YT (AMER CERAMIC SOC, 2003)
During a rapid thermal annealing process at 850degreesC in a N-2 ambient, an as-deposited amorphous YMnO3 thin film on Si (100) substrates was crystallized with two distinct layers. High-resolution transmission electron microscopy showed a top layer of c-axis-oriented Y-MnO3 and a bottom layer of polycrystalline YMnO3 in the 100-nm-thick YMnO3 thin film. The abrupt change of the crystalline orientation from the c-axis-preferred orientation to the random orientation is caused primarily by high stress induced by the c-axis-oriented YMnO3 layer. High-resolution X-ray diffraction showed that the c-axis-oriented YMnO3/polycrystalline YMnO3 structure effectively relieved the stress.
Keywords: NONVOLATILE MEMORY DEVICES; FERROELECTRIC PROPERTIES; SI; MICROSTRUCTURE; CANDIDATE; GROWTH